2017
DOI: 10.1111/pce.13095
|View full text |Cite
|
Sign up to set email alerts
|

Interdependency of efficient nodulation and arbuscular mycorrhization inPiptadenia gonoacantha,a Brazilian legume tree

Abstract: Tripartite interactions between legumes and their root symbionts (rhizobia and arbuscular mycorrhizal fungi, AMF) are poorly understood, although it is well established that only specific combinations of symbionts lead to optimal plant growth. A classic example in which to investigate such interactions is the Brazilian legume tree Piptadenia gonoacantha (Caesalpinioideae), for which efficient nodulation has been described as dependent on the presence of AMF symbiosis. In this study, we compared the nodulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 67 publications
3
20
0
1
Order By: Relevance
“…We found that plants in tripartite interactions had a significantly higher root and shoot biomass, N tissue concentrations and contents, and P contents than plants that were only colonized by rhizobia or AM fungi (Figures a,b; c,d; and S3a,c). Synergistic responses in tripartite interactions have also been described by other authors especially under low P and N supply conditions (Bournaud et al, ; Larimer et al, ). The dual inoculation with rhizobia and AM fungi can lead to higher photosynthetic rates and improves the harvest index (proportion of seed yields in relation to the total plant biomass) of legumes (Afkhami & Stinchcombe, ; Kaschuk, Kuyper, Leffelaar, Hungria, & Giller, ).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We found that plants in tripartite interactions had a significantly higher root and shoot biomass, N tissue concentrations and contents, and P contents than plants that were only colonized by rhizobia or AM fungi (Figures a,b; c,d; and S3a,c). Synergistic responses in tripartite interactions have also been described by other authors especially under low P and N supply conditions (Bournaud et al, ; Larimer et al, ). The dual inoculation with rhizobia and AM fungi can lead to higher photosynthetic rates and improves the harvest index (proportion of seed yields in relation to the total plant biomass) of legumes (Afkhami & Stinchcombe, ; Kaschuk, Kuyper, Leffelaar, Hungria, & Giller, ).…”
Section: Discussionsupporting
confidence: 68%
“…It is well established that a synergy of benefits can occur and that the host plant can gain more from tripartite interactions than from single inoculations with either symbiont (Afkhami & Stinchcombe, 2016;Antunes, de Varennes, Zhang, & Goss, 2006;Bournaud et al, 2017;Meng et al, 2015;Yasmeen, Hameed, Tariq, & Ali, 2012). The N-fixing capability of rhizobia is often limited by the P availability, and AM fungi can stimulate root nodulation, nitrogenase activity, and BNF through their positive effect on plant P nutrition (Ding et al, 2012;Owino-Gerroh, Gascho, & Phatak, 2005;Püschel et al, 2017;Vesterager, Nielsen, & Hogh-Jensen, 2006).…”
mentioning
confidence: 99%
“…In natural environments, legume roots form tripartite interactions and are simultaneously colonized by both AM fungi and rhizobia [7,79]. Tripartite interactions have been shown to improve plant productivity, seed yield, P and N acquisition, and photosynthetic rates [10,80,81]. The rhizobial nitrogenase complex requires at least 16 ATP to reduce one N 2 molecule into two NH 3 .…”
Section: Tripartite Symbiosis With Arbuscular Mycorrhizal Fungi and Rmentioning
confidence: 99%
“…Consequently, nodules act as strong P sinks in legume root systems to provide sufficient P resources to the bacteroids for optimum BNF [79,82]. Since AM fungi are able to improve the P nutrition of legume plants, AM fungi can increase the BNF by root nodules by at least 50% [10]. Nonmycorrhizal soybean plants have lower nodule numbers and weights and particularly under low P supply lower N fixation rates [7,83].…”
Section: Tripartite Symbiosis With Arbuscular Mycorrhizal Fungi and Rmentioning
confidence: 99%
See 1 more Smart Citation